The Satisfaction of Health Students to Online Learning Methods During the Covid-19 Pandemic - Rostime Hermayerni Simanullang; Afnijar Wahyu; Hendry Kiswanto Mendrofa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The Covid 19 pandemic has changed the method of learning in the world of health. The United Nations Educational, Scientific, and Cultural Organization (UNESCO) announced that 1.2 billion students worldwide have been affected by school closures at universities due to the Covid-19 outbreak. Online learning (DARING) is increasingly being used during the Covid-19 pandemic. The process of using DARING requires adaptation for students, this is a new experience. The purpose of this study was to evaluate the satisfaction of health students in using e-Learning methods during Covid-19. This research method is a descriptive survey using a questionnaire about student satisfaction with online learning methods. A total of 130 students participated in this study. The results of this study indicated that 39.3% of the students expressed dissatisfaction, 27.7% of the students stated that they were very dissatisfied, 23.1% of the students stated that they were satisfied and 10.0% of the students stated that they were very satisfied. The conclusion in this study is that the majority of health students expressed dissatisfaction in implementing e-Learning methods during pandemic Covid-19 in Medan.Abstrak: Pandemi Covid 19 telah mengubah metode pendidikan di dunia Kesehatan. United Nations Educational, Scientific, and Cultural Organization (UNESCO) mengumumkan bahwa 1,2 milliar siswa di seluruh dunia telah terkena dampak penutupan sekolah di Universitas karena wabah Covid-19. Pembelajaran Dalam Jaringan (DARING) semakin banyak di gunakan selama pandemic Covid 19. Proses penggunanan DARING membutuhkan adaptasi bagi mahasiswa, hal ini merupakan pengalaman baru. Tujuan penelitian ini adalah untuk mengevaluasi kepuasan mahasiswa kesehatan dalam menggunakan pembelajaran Daring selama Covid 19.  Metode penelitian ini adalah Survei deskriptif menggunakan kuesioner tentang kepuasan mahasiswa dengan metode pembelajaran Daring. Sebanyak 130 mahasiswa berpartisipasi dalam penelitian ini. Hasil penelitian menunjukkabahwa 39.2 % mahasiwa meyatakan tidak puas, 27.7 % mahasiswa menyatakan sangat tidak puas, 23.1 % mahasiswa menyatakan puas dan 10.0 % mahasiswa menyatakan sangat puas. Simpulan dalam penelitian ini adalah bahwa mahasiwa kesehatan mayoritas menyatakan tidak puas dalam melaksanakan metode pembelajaran Daring (Dalam Jaringan).